Erratum: BOB CAT: A Large-Scale Review and Delphi Consensus for Management of Barrett's Esophagus With No Dysplasia, Indefi nite for, or Low-Grade Dysplasia (American Journal of Gastroenterology (2015) 110 (xx) DOI: 10.1038/ajg.2015.55) - Bennett, Cathy; Moayyedi, Paul; Corley, Douglas A.; DeCaestecker, John; Falck-Ytter, Yngve; Falk, Gary; Vakil, Nimish; Sanders, Scott; Vieth, Michael; Inadomi, John; Aldulaimi, David; Ho, Khek Yu; et al. (American Journal of Gastroenterology, 2015)
NICE has accredited the process used by the BOB CAT Consortium to produce its 'BOB CAT: A Large-Scale Review and Delphi Consensus for Management of Barrett's Esophagus With No Dysplasia, Indefi nite for, or Low-Grade Dysplasia' guidance. Accreditation is valid for 5 years. More information on accreditation can be viewed at www.evidence.nhs.uk . For full details on our accreditation visit www.nice.org.uk/accreditation.
CRIS-Team Scopus Importer:2025-03-05